2016
DOI: 10.1002/hipo.22651
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and striatal M1‐muscarinic acetylcholine receptors are down‐regulated following bilateral vestibular loss in rats

Abstract: Permanent vestibular loss has detrimental effects on the hippocampus, resulting in a disruption to spatial learning and memory, hippocampal theta rhythm and place cell field spatial coherence. Little is known about the vestibular system-related hippocampal cholinergic transmission. Since the pharmacological blockade of muscarinic acetylcholine (ACh) receptors within the hippocampus produces deficits in learning and memory, we hypothesized that ACh receptors may at least partly support the integration of vestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…In theory, the elevation in cortisol could be attributed to both the stress of disturbed sleep patterns and to vestibular dysfunction, and it has been shown that chronically elevated levels of cortisol may contribute to hippocampal atrophy. This last point was elaborated further in other studies that found correlations between hippocampal atrophy and bilateral vestibular loss (Van Cruijsen, Hiemstra et al 2007, Aitken, Benoit et al 2016, Balabhadrapatruni, Zheng et al 2016, Seo, Kim et al 2016.…”
Section: Discussionmentioning
confidence: 53%
“…In theory, the elevation in cortisol could be attributed to both the stress of disturbed sleep patterns and to vestibular dysfunction, and it has been shown that chronically elevated levels of cortisol may contribute to hippocampal atrophy. This last point was elaborated further in other studies that found correlations between hippocampal atrophy and bilateral vestibular loss (Van Cruijsen, Hiemstra et al 2007, Aitken, Benoit et al 2016, Balabhadrapatruni, Zheng et al 2016, Seo, Kim et al 2016.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have found neurochemical changes in the striatum following bilateral vestibular loss in rats. Aitken et al (72), using receptor autoradiography, reported that M 1 muscarinic acetylcholine receptors, which mediate many of the excitatory effects of acetylcholine, decreased in density in the striatum and the hippocampus at 30 days (but not 7 days) following bilateral vestibular loss induced by intratympanic injection of sodium arsanilate. In a related study, Benoit et al (73), using flow cytometry, demonstrated that the number of neurons expressing M 2 acetylcholine receptors, which mediate many of the inhibitory effects of acetylcholine, underwent a significant increase at 30 days (but not 7 days) in the striatum and hippocampus following bilateral vestibular loss.…”
Section: Neural Circuitry Underlying Effects Of Vestibular Stimulatiomentioning
confidence: 99%
“…In this line, animal models of inner ear damage are well suited to investigate lesion-induced cerebral plasticity in correlation to behavioural markers 15 . Bilateral vestibular deafferentation in rodents results in a typical clinical syndrome with gait ataxia and postural imbalance, which partially recovers over weeks due to adaptation and sensory substitution [16][17][18] . In contrast, spatial orientation de cits persist over time 19 .…”
Section: Introductionmentioning
confidence: 99%